Perubahan Perilaku Ibu Hamil Trimester III dalam Mengonsumsi Tablet Fe Berdasarkan Stage of Change - Berlianti Putri Audina; Sugijati; Kiswati (Indonesian Journal Publisher, 2025)
Background: Compliance with taking Fe tablets is the behavior of pregnant women who obey the instructions or rules given by health workers during pregnancy. Many pregnant women do not comply with the recommendations for consuming Fe tablets given by health workers. This behavior occurs due to factors such as knowledge, education, and side effects of tablets, so that the purpose of giving them is not achieved. According to data from the Jember District Health Service in 2023, coverage of pregnant women who received Fe3 tablets (pregnant women up to the third trimester received 90 blood supplement tablets) was 83.13% and had decreased compared to 2022, which was 88.9%. The preliminary study results showed that 7 out of 10 pregnant women in the third trimester in the Sukowono Health Center Working Area still did not regularly consume Fe tablets. The purpose of the study was to determine changes in the behavior of third trimester pregnant women in taking Fe tablets based on the stage of change. Method:The research design uses pre-experimental research with one group pre and posttest. The population used all pregnant women in the third trimester, as many as 60 people. The sampling technique was proportionate random sampling of 38 respondents. Data collection uses a questionnaire. Results: Data analysis using the Wilcoxon test. The research results showed that the majority of pregnant women before the intervention were in the contemplation stage, and after the intervention, in the action stage. There is a change in the behavior of third-trimester pregnant women in consuming Fe tablets based on the stage of change, with a p-value = 0.000 < 0.05. Conclusion: The behavior of pregnant women in consuming Fe tablets will increasingly become an action and lead to maintenance, so efforts need to be made to make pregnant women aware of regular consumption through providing education and assistance by health workers or families.